Microbiology quality of fresh, freshly slaughtered, frozen and chilled poultry carcasses - Abdul Aziz, Saleha; Kasim, Basri (Persatuan Doktor Veterinar Malaysia, 1985)
Aerobic Plate Count (APC), Enterobacteriaceae and coagulase positive Staphylococcus aureus counts were made on (a) fresh poultry carcasses sold in open markets, (b) freshly slaughtered carcasses, (c) frozen carcasses from the University farm produce outlet and (d) chilled carcasses from supermarkets. Samplings were done weekly over an LBweek period. Fresh carcasses showed the highest APC, the mean was 3630 xl 03 per cm2 while frozen carcasses showed the lowest, 240 x 103 per ems, A significant difference in APC was found among poultry carcasses marketed under the 4 different conditions. Also, significant differences were found in Enterobacteriaceae and S. aureus counts where the mean per type of carcass for Enterobacteriaceae counts per cm? for fresh, freshly slaughtered, frozen and chilled carcasses were 1090 x 103, 9.12 x 103, 5.62 X 103 and 4.27 x 103 respectively; while the mean per type of carcass for S. aureus counts per ems were 2S.S0 x 103, 0.72 X 103, 0.11 X 103 and 0.15 x 103, respectively. Also, among the poultry carcasses, the fresh ones had the highest percentage positive for presence of Enterbacteriaceae (100%) and S. aureus (73.7%), while the lowest was found with chilled carcasses (26. 7%and 40.0%, respectively).